Whose side are you on? - Sheehan, Thomas (2018)
The modern era is characterised by an emphasis on one of our two «sides», the analytic «side», at the cost of our more synthetic and intuitive «side». The negative consequences of the excessive dominance of instrumental reason have been eloquently described by various important thinkers, including Max Weber, Martin Heidegger and Jürgen Habermas. The neglect of our imaginative abilities could impoverish our artistic and scientific productions and hinder our access to the religious experience. The solution requires the promotion of those abilities which are being progressively marginalised in the current educational system, in an attempt to achieve a balance or harmony between the various cognitive capacities of the human being.